Popularizing Electoral Politics: Change in the 2016 U.S. Presidential Race - Heiskanen Benita; Butters Albion M. (European Association for American Studies (EAAS), 2022)
This special issue of the European Journal of American Studies examines the popularization of electoral politics during the 2016 U.S. Presidential Election. The popularization processes include the rise of populism penetrating the U.S. political landscape; a media focus on human interest, rather than policy substance questions; personality politics and celebrity culture at the center stage of the election; and the appropriation and dissemination of popular culture discourses by social media users. The articles draw from transdisciplinary American Studies approaches to tackle a range of issues which arose during the election, from contestations of “American-ness” and competing narratives of truth—or “post-truth”—to questions of campaign finance and displays of violence, verbal and physical. The issue also takes a closer look at specific expressions of popular culture as reflected in the media, specifically in relation to the rise of nativism and the alt-right movement, the political impact of comedy on the election, and the significance of memes in the battle over image and meaning-making. The processes of popularizing electoral politics of the 2016 race had distinct consequences, not only in shaping political culture as we know it, but also in destabilizing established rules of political conduct.